THE ROLE OF DATA AND ANALYTICS IN MODERN POLITICAL CAMPAIGNS: A LITERATURE REVIEW ON EFFECTIVENESS AND ETHICS - Bikah Kusti Noviani; Loso Judijanto; Al-Amin (ADISAM Publisher, 2024)
Advances in information technology have changed the way political campaigns are conducted, enabling the use of big data and advanced analytics to understand and influence voters. The review in this research uses the literature method. The results show that the use of data and analytics can improve campaign efficiency and the effectiveness of political messages. However, there are also ethical challenges such as privacy concerns, the risk of manipulation, and the potential for increased political polarisation. In conclusion, although data and analytics provide great opportunities to improve campaign strategies, their use must be balanced with appropriate ethical and regulatory considerations.